2019
DOI: 10.1002/poc.3942
|View full text |Cite
|
Sign up to set email alerts
|

A detailed theoretical simulation about the excited state dynamical process for the novel (benzo[d]thiazol‐2‐yl)‐5‐(9H‐carbazol‐9‐yl)phenol molecule

Abstract: Given that molecular excited state dynamical process plays important roles in designing and developing novel applications in recent years. In this work, based on density functional theory (DFT) and time‐dependent density functional theory (TDDFT) methods, we theoretically explored the novel (benzo[d]thiazol‐2‐yl)‐5‐(9H‐carbazol‐9‐yl)phenol (HBT‐Cz) system about its excited state behaviors. Via simulating the electrostatic potential surface (EPS) of HBT‐Cz structure, we confirm the formation of intramolecular h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 68 publications
1
3
0
Order By: Relevance
“…The shortening of the hydrogen-bond length in the E-S 1 states indicates that the N center has more affinity toward the proton in the excited state, which would lead to ESIPT. The N···H bond lengths calculated in both HBT-Fl1 and HBT-Fl2 for S 0 and S 1 states of E form are comparable to ones previously reported for other HBT derivatives . In both cases, the E-S 1 state corresponds to the π–π* excitation of an electron from the highest occupied molecular orbital (HOMO) to the lowest unoccupied molecular orbital (LUMO).…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…The shortening of the hydrogen-bond length in the E-S 1 states indicates that the N center has more affinity toward the proton in the excited state, which would lead to ESIPT. The N···H bond lengths calculated in both HBT-Fl1 and HBT-Fl2 for S 0 and S 1 states of E form are comparable to ones previously reported for other HBT derivatives . In both cases, the E-S 1 state corresponds to the π–π* excitation of an electron from the highest occupied molecular orbital (HOMO) to the lowest unoccupied molecular orbital (LUMO).…”
Section: Resultssupporting
confidence: 80%
“…The photophysical properties of ESIPT dyes in different solvents can often provide vital information regarding the activation energy required to achieve intramolecular proton transfer. , Previous theoretical studies have shown that hydrogen bonding between nitrogen and hydrogen can promote the ESIPT process . Solvent reorganization accompanies hydrogen bonding between the dye and the solvent molecules. ,, This can further induce an external barrier to the proton transfer, which, in addition to the intrinsic enol–keto energy barrier, may lead to dual emission from both enol and keto species.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations